A potential study of Synsepalumdulcificum (Sapotaceae) "miracle berry" / Fatimah Abdol Latif, Sarina Hashim and Zairus Ismail - Abdol Latif, Fatimah; Hashim, Sarina; Ismail, Zairus (2011)
Synsepalumdulcificum or Miracle berry plant is a slow-growing shrub belonging to Sapotaceae. The aims of the study were to identify the morphology of S. dulcificum and to examine the seed germination through in vitro propagation. Mature plants of S. dulcificum were obtained from Tekam Plantation, Jerantut, Pahang. The 20 cm stem cutting was used to study the phyllotaxis and to investigate the feature of flower and fruit. To determine the performance of seed culture, seeds sterilization done by surface-sterilization with 95% ethanol for 5 min, 20% NaOCI for 20 minutes. Then, the sterile seeds were maintained on Murashige and Skoog (MS) basal medium. The record of shoots and roots formation were taken by direct observation. This study shows that S. dulcificum have a deep green, 10-13 cm elongated thin leaves with entire margin. The flowers are born axially, with small white flowers about 1 cm length during opening, change to creamy yellow, then black when past mature. The plants produced 2-3 cm ellipsoid fruits with a single seed. The seeds were used for in vitro propagation. Shoots and roots started to form after 16 weeks of culture incubation. Propagation was successfully done through seeds in the MS basal medium. Anyhow, further studies on the modifications of the in vitro physical and chemical environments of the nodal culture are recommended to enhance propagation of the plants. This study indicates that S. dulcificum has a great potential in landscaping because of their evergreen and slow growth rate, so that it does not grow higher. Seeds culture can increase the number of seedlings for plant lovers, so it can overcome the problem of slow sprouting rate of the plants.